1987
DOI: 10.1177/00220345870660010801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water-soluble Components of Cheese on Experimental Caries in Humans

Abstract: The effect of water-soluble components of extra-old Cheddar cheese on experimental caries was tested by means of the seven-day intraoral cariogenicity test (ICT). Two bovine enamel blocks were placed in each buccal flange of the dental appliances of five volunteers. One side of each appliance (experimental) was dipped in a 25% water extract of the cheese for five min, while the other side (control) was dipped in de-ionized water. Immediately thereafter, the appliance was returned to the subject's mouth, and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 17 publications
1
32
1
2
Order By: Relevance
“…Several lines of evidence have shown that consumption of a cube of cheese following carbohydrate foods may protect against dental caries, probably by increasing the plaque calcium concentration [1][2][3][4] and the pH of plaque. 1 However, cheese is not usually consumed alone following a meal and it is not known whether cheese, as it is habitually consumed, as part of a cooked mixed meal, is protective.…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Several lines of evidence have shown that consumption of a cube of cheese following carbohydrate foods may protect against dental caries, probably by increasing the plaque calcium concentration [1][2][3][4] and the pH of plaque. 1 However, cheese is not usually consumed alone following a meal and it is not known whether cheese, as it is habitually consumed, as part of a cooked mixed meal, is protective.…”
Section: Researchmentioning
confidence: 99%
“…3 More recently, a study of 179 children aged 7 to 9 years, showed that consumption of 5 g of cheese following breakfast for a period of 2 years was effective in reducing caries. 9 In one extensive dietary survey it was shown that children who were caries-free consumed significantly more cheese than children who were more caries-prone.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Derived from the milk protein, casein, and digested by the enzyme trypsin, one of the most important features of CPP is their abil ity to stabilise amorphous calcium phos phate (ACP), preventing its precipitation in solution. The spectrum of action of the CPP-ACP complex is broad, buffer ing pH, preventing demineralisation and allowing for remineralisation.…”
Section: Discussionmentioning
confidence: 99%